Assessment of Avoidable Losses Caused by Leaf Webber and Capsule Borer (Antigastra Catalaunalis Dup.) in Promising Sesame Varieties - Sundria, Man Mohan; Pandey, Shalini; Geat, Neelam; Kumhar, S. R. (Annals of Arid Zone, 2022)
An experiment was conducted during the kharif seasons of 2018 and 2019with varieties viz., RT 346, RT 351, TKG 306, TKG 308, Rama, VRI 1, GT 10 and TKG22 of sesame (Sesamum indicum L.) to assess the avoidable loss in seed yield due to leafwebber and capsule borer under rainfed conditions at ARS, Mandor. The performanceof all the promising sesame varieties grown under protected conditions were foundsignificantly superior over the unprotected conditions, except in case of two varietiesviz., TKG-308 and VRI-1 at capsule stage only. The varieties viz., RT 351, TKG 308and GT 10 were found significantly superior over all other varieties of sesame grownunder both the protected and unprotected conditions. Avoidable loss recorded rangedfrom 25.51 to 61.45% in different varieties under protected condition in comparison tounprotected conditions, maximum in RT 351 and minimum in VRI 1 due to leaf webberand capsule borer. The pest caused significant loss in seed yield under unprotectedcondition in comparison to protected condition. The varieties viz., TKG 308, RT 351 andGT 10 performed good under unprotected conditions and gave highest seed yield, thevariety GT 10 stands first in respect to record lowest damage (9.58%, 15.89% and 5.40%at vegetative, flowering and capsule stage, respectively) under unprotected conditions.Varieties viz., RT 351, TKG 308 and GT 10 gave highest seed yields of 444 kg ha-1, 433kg ha-1 and 397 kg ha-1, respectively, under protected condition. Overall, all the varietiesperformed well in protected conditions and their yield potential were also increased.